Can THEM6 targeting stop resistance to prostate cancer treatment?. Issue 3 (2nd February 2022) - Chattopadhyay, Mrittika; Germain, Doris
Abstract : Prostate cancer (PCa) clinical management relies heavily on androgen‐deprivation therapy (ADT). However, despite experiencing initial clinical benefit, patients getting ADT for non‐resectable PCa eventually relapse and develop fatal castration‐resistant PCa (CRPC). Multiple mechanisms of acquired resistance to treatment have been reported, including metabolic adaptation (Marine et al, 2020). Notably, activation of the endoplasmic reticulum (ER) unfolded protein response (UPR) has been associated with oncogenic transformation (Hart et al, 2012), tumor progression, metastasis dissemination, and resistance to therapy (Chen & Cubillos‐Ruiz, 2021). Targeting different branches of ER UPR has been found to be an effective tool against aggressive PCa (Nguyen et al, 2018; Sheng et al, 2019). Therefore, a better understanding of these pathways may lead to the identification of novel drug targets. Abstract : D. Germain and M. Chattopadhyay discuss the study by Blomme et al, in this issue of EMBO Mol. Med., that shows that THEM6 reprograms lipid metabolism to support resistance to androgen‐deprivation therapy, and is a promising target for the treatment of castration‐resistant prostate cancer.